Infection Control and Viral Reduction: A Review of Strategies, Responsibilities, and Impacts of Medical Staff - Alqashanin, Fahad Mesfer Ali; Alyami, Farhan Mahdi Mohammed; Alnemi, Hassan Hussain Ali; Alharthi, Abhal Nasser Ali; Sultan, Samaher Nasser ALI; Asiri, Yasmin Ali Yahya; Albarqi, Maram Mohammed Ahmed; Hussain, Abeer Ali Abdullah; Alsadrani, Hanan Suliman; Alqhtani, Hadi Fahad Dashen (Journal of Posthumanism, 2024)
This review explores the essential roles of medical staff in infection prevention and viral reduction within healthcare settings. It synthesizes evidence from clinical studies, organizational frameworks, and international guidelines to examine how nurses, physicians, laboratory professionals, and support teams contribute to infection control. The paper highlights the importance of adherence to standard precautions, use of personal protective equipment (PPE), environmental hygiene, vaccination advocacy, and leadership in infection prevention programs. Moreover, it assesses the challenges posed by emerging infectious diseases and antimicrobial resistance, and outlines strategic recommendations for improving compliance, training, and culture of safety. The findings underline that infection control is a multidisciplinary responsibility requiring collaboration, evidence-based practice, and continual education to reduce viral transmission and safeguard both patients and healthcare workers.